2014
DOI: 10.1159/000367963
|View full text |Cite
|
Sign up to set email alerts
|

Current and Best Practices of Genetic Testing for Maturity Onset Diabetes of the Young: Views of Professional Experts

Abstract: Aims: Currently, many patients with maturity onset diabetes of the young (MODY) are undiagnosed or misdiagnosed with type 1 or 2 diabetes. This study aims to assess professional experts' views on factors which may influence the current practice of genetic testing for MODY and to explore next steps toward best practice. Methods: Twelve semistructured interviews were conducted with professional experts. These experts included physicians with potential or actual experience with genetic testing for MODY, represent… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
21
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 17 publications
(22 citation statements)
references
References 30 publications
1
21
0
Order By: Relevance
“…Despite the availability of genetic testing, there are a significant number of patient-and physician-related factors that may be prohibitive to uptake, including the perceived lack of possibilities for treatment (if coexistent MODY and T2D develop over time, many would argue that it may not change management if hyperglycaemia is mild; however, we believe that it makes a difference to management and monitoring) and prevention, cost implications of a positive diagnosis to patients, and lack of awareness of MODY as a diagnosis. 40 These factors should all be discussed with the patient when considering genetic or genomic testing. The patient should be counselled regarding the treatment implications of a positive diagnosis, including the possibility that they may have not required the treatment they were prescribed many years prior.…”
Section: Resultsmentioning
confidence: 99%
“…Despite the availability of genetic testing, there are a significant number of patient-and physician-related factors that may be prohibitive to uptake, including the perceived lack of possibilities for treatment (if coexistent MODY and T2D develop over time, many would argue that it may not change management if hyperglycaemia is mild; however, we believe that it makes a difference to management and monitoring) and prevention, cost implications of a positive diagnosis to patients, and lack of awareness of MODY as a diagnosis. 40 These factors should all be discussed with the patient when considering genetic or genomic testing. The patient should be counselled regarding the treatment implications of a positive diagnosis, including the possibility that they may have not required the treatment they were prescribed many years prior.…”
Section: Resultsmentioning
confidence: 99%
“…The issues of the costs of genetic testing and healthcare benefits are recurrently debated so as to improve practical guidelines for both patient care and educational perspectives . A simulation model for diabetes complications was used to evaluate the cost‐effectiveness of a genetic testing policy for mutations in GCK /MODY2, HNF1A /MODY3, and HNF4A /MODY1 in a hypothetical case cohort with a MODY prevalence of 2 % .…”
Section: Current Challenges In Molecular Genetic Diagnosis Of MDmentioning
confidence: 99%
“…The issues of the costs of genetic testing and healthcare benefits are recurrently debated so as to improve practical guidelines for both patient care and educational perspectives. 47 A simulation model for diabetes complications was used to evaluate the cost-effectiveness of a genetic testing policy for mutations in GCK/ MODY2, HNF1A/MODY3, and HNF4A/MODY1 in a hypothetical case cohort with a MODY prevalence of 2 %. 48 With a conservative interpretation of costeffectiveness and based on incremental cost-effectiveness ratio thresholds in the US, model sensitivity analysis showed that small increases in MODY prevalence in the case cohort (from 2 % to 6 %) made the genetic screening policy cost-effective.…”
Section: Current Challenges In Molecular Genetic Diagnosis Of MDmentioning
confidence: 99%
“…Even if patients had whole-genome sequence data already available in their medical records, this treatment effect is still too small to be clinically useful. For MODY, which often has a clear genetic cause, most cases appear to be undiagnosed, in part because of uncertainty from clinicians about the clinical benefits of genetic testing (132). Making treatment decisions based on genetic tests that lack clinical validity, clinical utility, or both can have unintended consequences, including withholding beneficial treatments, an unnecessary increase in costs, or the use of drugs with harmful effects.…”
Section: Framework For Evaluating a Genomic Testmentioning
confidence: 99%